2014
DOI: 10.1021/jp411086f
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubes With Well-Defined Structure: Single- and Double-Walled Imogolites

Abstract: We have investigated the structure and electronic structure of single-and double-walled imogolite nanotubes with Ge and Si as group IV element. While it is known from experiment, and in the case of single-walled tubes confirmed by theory, imogolite nanotubes are monodisperse in diameter. We show that imogolite tubes are also showing a preferred chirality (zigzag), resulting from the hydrogen-bond network on the tube surfaces, and that there is an exceptionally stable form of intertube interaction that supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 44 publications
7
48
1
Order By: Relevance
“…In all types of defects, the Young's modulus of the AlSiNTs decreased with an increase in the number of defects (Figure a). The Young's modulus of the defect‐free AlSiNT is approximately 340 GPa, which is in agreement with previous reports . The decrease in the Young's modulus was most pronounced in Defect 5 (reduction rate=0.57 GPa per defect site) and least pronounced in Defect 2 (reduction rate=0.088 GPa per defect site).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In all types of defects, the Young's modulus of the AlSiNTs decreased with an increase in the number of defects (Figure a). The Young's modulus of the defect‐free AlSiNT is approximately 340 GPa, which is in agreement with previous reports . The decrease in the Young's modulus was most pronounced in Defect 5 (reduction rate=0.57 GPa per defect site) and least pronounced in Defect 2 (reduction rate=0.088 GPa per defect site).…”
Section: Resultssupporting
confidence: 91%
“…High dispersity makes AlSiNTs amenable to aqueous‐phase processing and compatible with hydrophilic polymeric materials, such as poly(vinyl alcohol) . Several computational studies have reported that AlSiNTs possess a Young's modulus of approximately 340 GPa and a shear modulus of 160 GPa . However, these calculations are based on a defect‐free crystalline model, which is very likely to overestimate the actual mechanical strength .…”
Section: Introductionsupporting
confidence: 91%
“…The diameter of the AlSiNTs is indicated by the number of unit cells in the circumference, denoted by N. AlSiNTs with 11 unit cells in the circumference were denoted as AlSiNT11 and the remainder can be deduced by analogy. 53,54 In addition, the Young's modulus of AlSiNTs in this work was consistent with the results from previous reports (in a range of 122-479 GPa), [47][48][49] which was determined by density-functional based tight-binding (DFTB), density functional theory (DFT), or the self-consistent charge density-functional based tight-binding (SCC-DFTB) methods. The CNTs discussed in this study are single-walled carbon nanotubes with a chirality of (14,14), denoted as SWCNT (14,14).…”
Section: Resultssupporting
confidence: 90%
“…Thus far, this has greatly limited their applicability in large-scale systems and devices. [47][48][49] The lack of reliable mechanistic research on these mechanical properties has greatly retarded the advancement of AlSiNTs as reinforcing materials for nanocomposites. In particular, single-walled aluminosilicate nanotubes (AlSiNTs), also known as the synthetic imogolites, have been attracting considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, computational tools play a critical role in the investigation of nanotube materials [59,60] . For example, calculations based on density functional theory (DFT) and force fields have been performed to discover the probable dimensions and electrical properties of aluminosilicate and aluminogermanate nanotubes [33,[61][62][63][64][65][66] . Molecular dynamics (MD) and grand canonical Monte Carlo (GCMC) simulations have been employed to investigate the diffusion and adsorption properties of various molecules in nanotubes [32,36,37] .…”
Section: Introductionmentioning
confidence: 99%